The Effect of Differentiated Learning on Science Learning Outcomes of Fifth-Grade Students at SD Inpres Unggulan Toddopuli, Makassar City - Marwa Malik; Muhammad Irfan; Abdul Rahman (Program Studi PGSD FIP UNM, 2026)
This study aimed to examine the effect of differentiated instruction on improving the learning outcomes of fifth-grade students in the IPAS subject at SD Inpres Unggulan Toddopuli. The study employed a quasi-experimental method using a nonequivalent control group design. The population consisted of all fifth-grade students at SD Inpres Unggulan Toddopuli. The sampling technique used was total sampling, involving 30 students from class VA and 30 students from class VB. Data were collected through observation sheets on the implementation of differentiated instruction and multiple-choice written tests consisting of a pretest and a posttest. Data analysis techniques included descriptive statistics and inferential statistics using the Independent Samples t-test. The findings showed that: (1) the implementation of differentiated instruction was categorized as very good; (2) the IPAS learning outcomes of students in the experimental class before treatment were categorized as low, while after the implementation of differentiated instruction, the students’ learning outcomes improved to the good category; and (3) the Independent Samples t-test results indicated a significant difference between the posttest scores of the experimental group and the control group. These findings indicate that differentiated instruction improved students’ learning outcomes. Therefore, it can be concluded that differentiated instruction has a positive effect on the learning outcomes of fifth-grade students in the IPAS subject at SD Inpres Unggulan Toddopuli, Panakkukang District, Makassar City.